Creative and educational potential of living spaces - Bobić, Lidija; Krupić, Martina; Perić, Anka (Rethinking childhood II: child and space, 2026)
Active reflection by professional educators on children’s needs results in the creation of a spatial environment that is bound to encourage child’s creative enthusiasm. Therefore, it is crucial to emphasise that space, the so-called third educator, is an irreplaceable factor in the educational process. Space cannot be viewed as a separate category in the educational process; rather, it is part of the institution’s culture, teamwork, and the pursuit of a modern curriculum, so it should be viewed in the context of an institution for early and preschool education. A child’s need for exploration is expressed from an early age. The allure of space, didactic materials, and the natural environment is an incentive for a child’s creative expression. A child’s creativity is recognised by the original solutions that children demonstrate, and it is possible to observe it as a phenomenon, not only in children’s visual, two-dimensional or three-dimensional artwork, but also in their constructions while using various didactic materials, in verbal expressions, sound, etc. In this way, a child documents their efforts to explain to others what is hidden behind what they have created. It is not desirable to view the space, when designated for children, through the aesthetic arrangement of panels or walls with their creative works. Rather, that space should enable the progress of projects, the documentation created by children and adults, and the expression of experiences, thus recognising a new dimension in the learning of children, as well as of education. This research will provide examples of the use of various expressive media during the educational process and their benefits in relation to each individual child. Based on the presented examples, the paper offers an insight into educators’ interests in children’s activities, their understanding of children’s creativity, and the child’s need for self-expression through various forms of expressive media. The proposed model of the educational process implies a new approach to understanding children’s drawings and offers renewed meaning to the understanding children’s creative expression.